Harnessing p53 for targeted cancer therapy: new advances and future directions - Andrysik, Zdenek; Espinosa, Joaquin M (Transcription, 2025)
The transcription factor p53 is the most frequently impaired tumor suppressor in human cancers. In response to various stress stimuli, p53 activates transcription of genes that mediate its tumor-suppressive functions. Distinctive characteristics of p53 outlined here enable a well-defined program of genes involved in cell cycle arrest, apoptosis, senescence, differentiation, metabolism, autophagy, DNA repair, anti-viral response, and anti-metastatic functions, as well as facilitating autoregulation within the p53 network. This versatile, anti-cancer network governed chiefly by a single protein represents an immense opportunity for targeted cancer treatment, since about half of human tumors retain unmutated p53. During the last two decades, numerous compounds have been developed to block the interaction of p53 with the main negative regulator MDM2. However, small molecule inhibitors of MDM2 only induce a therapeutically desirable apoptotic response in a limited number of cancer types. Moreover, clinical trials of the MDM2 inhibitors as monotherapies have not met expectations and have revealed hematological toxicity as a characteristic adverse effect across this drug class. Currently, combination treatments are the leading strategy for enhancing efficacy and reducing adverse effects of MDM2 inhibitors. This review summarizes efforts to identify and test therapeutics that work synergistically with MDM2 inhibitors. Two main types of drugs have emerged among compounds used in the following combination treatments: first, modulators of the p53-regulated transcriptome (including chromatin modifiers), translatome, and proteome, and second, drugs targeting the downstream pathways such as apoptosis, cell cycle arrest, DNA repair, metabolic stress response, immune response, ferroptosis, and growth factor signaling. Here, we review the current literature in this field, while also highlighting overarching principles that could guide target selection in future combination treatments.
Keywords: cílená molekulární terapie; protinádorové látky; Neoplasms; combination therapy; protoonkogenní proteiny c-mdm2; nádorový supresorový protein p53; integrated stress response; nutlin; Proto-Oncogene Proteins c-mdm2; p53; Animals; lidé; Humans; zvířata; nelfinavir; Molecular Targeted Therapy; nádory; polytherapy; Tumor Suppressor Protein p53; Antineoplastic Agents